2016
DOI: 10.1074/jbc.m116.740464
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase A Subunit Balance Regulates Lipid Metabolism in Caenorhabditis elegans and Mammalian Adipocytes

Abstract: Protein kinase A (PKA) is a cyclic AMP (cAMP)-dependent protein kinase composed of catalytic and regulatory subunits and involved in various physiological phenomena, including lipid metabolism. Here we demonstrated that the stoichiometric balance between catalytic and regulatory subunits is crucial for maintaining basal PKA activity and lipid homeostasis. To uncover the potential roles of each PKA subunit, Caenorhabditis elegans was used to investigate the effects of PKA subunit deficiency. In worms, suppressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 92 publications
2
19
0
Order By: Relevance
“…Importantly, aak-2 loss of function and silencing significantly reduced the lifespan of age-1; gas-1 double mutants, whereas overexpression of AAK-2 promoted the survival of gas-1 mutants (Fig 3D and E,Appendix Fig S3A and B,and Dataset EV1). In C. elegans, kin-1 encodes the catalytic subunit of PKA, whereas kin-2 encodes for the regulatory one (Lee et al, 2016). In line with the IPA prediction, we found that age-1; gas-1 double mutants displayed an increased KIN-1 activity compared to gas-1 mutant animals ( Fig 3F).…”
Section: Iis Inhibition Reduces Atp-consuming Processes and Enhances supporting
confidence: 85%
See 1 more Smart Citation
“…Importantly, aak-2 loss of function and silencing significantly reduced the lifespan of age-1; gas-1 double mutants, whereas overexpression of AAK-2 promoted the survival of gas-1 mutants (Fig 3D and E,Appendix Fig S3A and B,and Dataset EV1). In C. elegans, kin-1 encodes the catalytic subunit of PKA, whereas kin-2 encodes for the regulatory one (Lee et al, 2016). In line with the IPA prediction, we found that age-1; gas-1 double mutants displayed an increased KIN-1 activity compared to gas-1 mutant animals ( Fig 3F).…”
Section: Iis Inhibition Reduces Atp-consuming Processes and Enhances supporting
confidence: 85%
“…Since genes in sugar metabolism seem particularly enriched in both the transcriptome and the proteome, we measured simple and complex carbohydrates using the phenol-sulfuric acid colorimetric assay. In C. elegans, kin-1 encodes the catalytic subunit of PKA, whereas kin-2 encodes for the regulatory one (Lee et al, 2016). We then overlapped IPA predictions from both transcriptomics and proteomics.…”
Section: Iis Inhibition Reduces Atp-consuming Processes and Enhances mentioning
confidence: 99%
“…Contrary to six6 whose role in testis remains so far unknown, akap11, although expressed in most studied tissues and cell types, has the strongest signal and suggested role in testis and sperm (47). It encodes A-kinase anchor protein 11, which interacts with type I and II regulatory subunits of protein kinase A (PKA) in order to tether PKA to discrete locations within a cell to control many essential functions, such as cell cycle (48) and lipid metabolism (49). Expression of Akap11 mRNA and protein is observed in sperm throughout spermatogenesis and its suggested association with cytoskeletal structure indicates its importance in the sperm function (47), and thus maturation.…”
Section: Introductionmentioning
confidence: 99%
“…Because GSA-1/Gαs often stimulates the production of cAMP and activation of PKA, we next explored a possible role for PKA in regulation of spermathecal contractility. KIN-1/PKA-C, is expressed in the spermathecal bag and the sp-ut valve [41]. Depletion of KIN-1/PKA-C resulted in significantly increased spermathecal occupancy (85% occupied, n=104; Fig.…”
Section: Gsa-1/gαs and Kin-1/pka-c Are Necessary For Proper Oocyte Trmentioning
confidence: 94%
“…Therefore, PKA-R acts as an inhibitor of PKA-C in the absence of cAMP. Once released, PKA-C interacts with multiple downstream effectors and regulates lipid metabolism [41], cell migration [42], and vasodilation [43], among many other functions [44]. In airway smooth muscle, PKA inhibits contraction by antagonizing Gαq mediated increases in Ca 2+ , as well as by phosphorylating and inhibiting Rho [45] and other regulators of contractility.…”
Section: Introductionmentioning
confidence: 99%